2012
DOI: 10.1007/s10549-012-1979-7
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of the 70-gene prognosis-signature (MammaPrint®) in hormone receptor-positive, lymph node-negative, human epidermal growth factor receptor type 2-negative early stage breast cancer in Japan

Abstract: The 70-gene prognosis-signature is validated as a good predictor of recurrence for hormone receptor-positive (ER+), lymph node-negative (LN-), human epidermal growth factor receptor type 2-negative (HER2-) early stage breast cancer (ESBC) in Japanese patient population. Its high cost and potential in avoiding unnecessary adjuvant chemotherapy arouse interest in its economic impact. This study evaluates the cost-effectiveness of including the assay into Japan's social health insurance benefit package. An econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…approaches to adjuvant therapy decision making. Similar findings were reported in the Japanese setting, where Kondo et al [46] investigated the cost-effectiveness of MammaPrint versus St. Gallen criteria from a societal perspective using an adaptation of a model previously used to evaluate the cost-effectiveness of Onco type DX ® . Projecting 10-year outcomes for a cohort of patients with ER+, LN− disease, aged 55 years at baseline from a Japanese cancer registry, MammaPrint was associated with an improvement in QALE of 0.06 QALYs and an additional cost of JPY 231,385 per patient, leading to an ICER of ~JPY 3.9 million (USD 43,000) per QALY gained.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…approaches to adjuvant therapy decision making. Similar findings were reported in the Japanese setting, where Kondo et al [46] investigated the cost-effectiveness of MammaPrint versus St. Gallen criteria from a societal perspective using an adaptation of a model previously used to evaluate the cost-effectiveness of Onco type DX ® . Projecting 10-year outcomes for a cohort of patients with ER+, LN− disease, aged 55 years at baseline from a Japanese cancer registry, MammaPrint was associated with an improvement in QALE of 0.06 QALYs and an additional cost of JPY 231,385 per patient, leading to an ICER of ~JPY 3.9 million (USD 43,000) per QALY gained.…”
Section: Resultssupporting
confidence: 60%
“…: EUR 1,130 increase in direct costsVersus Adjuvant! : EUR 4,614 per QALY gainedCost savings driven by avoided chemotherapy, which was greater versus St. Gallen and resulted in dominance Kondo et al [46]85JapanLN−, ER+, HER2−0.048 years gained versus St. GallenSocietal costs were JPY 231,385 per patient higher with MammaPrint than with St. GallenJPY 4,820,813 per life year gained versus St. Gallen55-year-old patients from a Japanese cancer registry0.060 QALYs gained versus St. GallenJPY 3,873,922 per QALY gained versus St. Gallen (willingness to pay threshold from a societal perspective is JPY 5,000,000 (approx. USD 55,000) per QALY gained)Results were sensitive to changes in assumptions on risk classification (low versus high) and distant recurrence ratesMammaPrint budget impact studies Zarca et al [47]N/AFranceLN 1–2Cost savings of EUR 9,043 per 100 patients per yearVersus current practice: MammaPrint is cost savingCost saving driven by reduced chemotherapy expenditureResults are sensitive to the relative use of St. Gallen and Adjuvant!MammaPrint versus Onco type DX ® cost-effectiveness studies Retèl et al [48]66NetherlandsTwo populations evaluated based on data previously collected by Thomassen et al and Fan et alThomassen: MammaPrint increased QALYs by 0.08 over Onco type DX ® Thomassen: Onco type DX ® increased direct cost by EUR 1,475Thomassen: MammaPrint dominates Onco type DX ® Fan: MammaPrint increased QALYs by 0.31 over Onco type DX ® Fan: Onco type DX ® increased direct cost by EUR 3,941Fan: MammaPrint dominates Onco type DX ® Uncertainty around these outcomes is high Yang et al [49]72USALN−, ER+MammaPrint increased QALYs by 0.097 over Onco type DX ® Oncotype DX ® increased direct cost by USD 6,284MammaPrint dominates Onco type DX ® Driver...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have yielded varying estimates ranging from cost-saving to an incremental cost-effectiveness ratio (ICER) of ∼US $60 000 per quality-adjusted life year (QALY). One Japanese study of the 70-gene assay [109] found an ICER of US $40 000 per QALY. Such assessments will be sensitive not only to the cost of the test, but to the net proportion of patients in whom testing leads to the omission of cytotoxic therapy, and to the cost of the cytotoxic regimen which would otherwise have been given.…”
Section: Breast Cancer Subtypesmentioning
confidence: 99%
“…In the subsequent sensitivity analysis in which the test was only administered to women with a Nottingham Prognostic Index of 3.4 or more, the ICER ranged from £6,053 to £29,569 per QALY gained compared with current practice. This uncertainty was also observed across the studies described by Rouzier et al 18 One study reported a decrease in direct costs of €7,430 compared with St. Gallen guidelines, 61 whereas two studies reported increases in direct cost of ¥231,385 62 and from $401 to $1,811 63 per patient compared with St. Gallen guidelines. Against Adjuvant!…”
Section: Evidence Overviewmentioning
confidence: 87%